Many de novo donor‐specific antibodies recognize β2‐microglobulin‐free, but not intact HLA heterodimers. (6th April 2016) - Michel, K.; Santella, R.; Steers, J.; Sahajpal, A.; Downey, F. X.; Thohan, V.; Oaks, M.
Abstract: Solid‐phase single antigen bead (SAB) assays are standard of care for detection and identification of donor‐specific antibody (DSA) in patients who receive solid organ transplantation (SOT). While several studies have documented the reproducibility and sensitivity of SAB testing for DSA, there are little data available concerning its specificity. This study describes the identification of antibodies to β2 ‐microglobulin‐free human leukocyte antigen (β2 ‐m‐fHLA) heavy chains on SAB arrays and provides a reassessment of the clinical relevance of DSA testing by this platform. Post‐transplant sera from 55 patients who were positive for de novo donor‐specific antibodies on a SAB solid‐phase immunoassay were tested under denaturing conditions in order to identify antibodies reactive with β2 ‐m‐fHLA or native HLA (nHLA). Antibodies to β2 ‐m‐fHLA were present in nearly half of patients being monitored in the post‐transplant period. The frequency of antibodies to β2 ‐m‐fHLA was similar among DSA and HLA antigens that were irrelevant to the transplant (non‐DSA). Among the seven patients with clinical or pathologic antibody‐mediated rejection (AMR), none had antibodies to β2 ‐m‐fHLA exclusively; thus, the clinical relevance of β2 ‐m‐fHLA is unclear. Our data suggests that SAB testing produces false positive reactions due to the presence of β2 ‐m‐fHLA and these can lead to inappropriate assignment of unacceptable antigens during transplant listing and possibly inaccurate identification of DSA in the post‐transplant period.